ASSESSING TOURISM STUDENTSâ€™ ENGLISH PROFICIENCY COMPETENCE BASED ON ASEAN COMMON COMPETENCY STANDARD - Kurniarini, Ni Nyoman Yunike; Waluyo, Untung; Yusra, Kamaludin (Yavana Bhasha : Journal of English Language Education, 2021)
This study is aimed to analyze the tourism studentsâ€™ English proficiency competence based on ASEAN Common Competency Standard (ACCS). The study used a descriptive qualitative method and the data were gained through English competency based workplace assessment for the students in three sub divisions at PDD Lombok Barat; hotel accommodation, culinary, and hotel engineering. The findings of the study showed that more than half of tourism students are still in the category of â€œlow competenceâ€ in attaining English competencies based on ACCS.